2021
DOI: 10.33369/jeet.5.2.188-200
|View full text |Cite
|
Sign up to set email alerts
|

Developing Students’ Speaking Skills through Flipped Classroom Model

Abstract: The aim of this study was to examine the impact of implementing flipped classroom model on students’ speaking skills. This research used quantitative method, the number of the sample were 34 of senior high school students which was taken purposively by using quasi-experimental research with before and after design. The whole online flipped classroom model was carried out, since the limitation to hold the actual face-to-face meeting at school, which still allow the students to interact face-to-face with each ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…The outcomes of the current study lend support to the findings of Sudarmaji et al (2021), who examined the impacts of applying the flipped classroom on students' speaking skills. Their outcomes showed that the online flipped model significantly developed the learners' speaking performances.…”
Section: Discussion Of the Studysupporting
confidence: 73%
See 1 more Smart Citation
“…The outcomes of the current study lend support to the findings of Sudarmaji et al (2021), who examined the impacts of applying the flipped classroom on students' speaking skills. Their outcomes showed that the online flipped model significantly developed the learners' speaking performances.…”
Section: Discussion Of the Studysupporting
confidence: 73%
“…Recently, Sudarmaji et al (2021) scrutinized the flipped instruction's impact on learners' speaking skills. To do this research, 34 senior high school students were chosen as the subjects of the investigation.…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…As stated by Sudarmaji et al (2021) , the flipped classroom increased pupils’ speaking performance level in which they could preview the pre-class materials and then practice their speaking skills. Subsequently, this result supported the findings of Mansor and Yunus (2017) who reported that pupils had more opportunities to practice the language with the aid of Blendspace.…”
Section: Discussionmentioning
confidence: 95%
“…According to Sudarmaji et al (2021), students should be asked to improve speaking skills on pronunciation, grammar, vocabulary, and fluency. In mastering speaking skill, the students should pay attention toward any proficiencies of speaking (Suparlan, 2021).…”
Section: Literature Review Speaking Skillsmentioning
confidence: 99%